Persons, situations, and emotions : an ecological approach - Brandstätter, Hermann; Eliasz, Andrzej (Series in affective science., 2001)
This book represents a social psychology approach to the study of emotion. The contributors will present empirical data using the ""time sampling"" or ""experience sampling"" technique developed by Brandstatter. This technique allows researchers to gain direct access to the phenomenological experience of subjects without the distorting effects of recall. Populations studied include bank employees, factory workers, housewives, and the unemployed.